Spaces of Fear – Angsträume. [Themenschwerpunkt] - (:unkn) unknown (Deutsches Institut für Urbanistik, 2020)
Dieses Themenheft befasst sich mit der dialektischen Beziehung zwischen der Räumlichkeit der Städte des 20. Jahrhunderts und einer bestimmten Emotion - der Angst: von einer körperlich spürbaren Angst vor Bombenangriffen, über die Angst vor Verkehrsunfällen, die in den stadtplanerischen Diskussionen instrumentalisiert wurden, bis hin zu diffuseren Ängsten, wie jenen die mit den Bahnhöfen assoziiert wurden, oder urbanen Angstprojektionen der Nachkriegszeit. Die Beiträge des Schwerpunkts: Mikkel Høghøj, Monika Motylińska: Spaces of fear in European cities of the 20th century / Angsträume in den europäischen Städten des 20. Jahrhunderts (S. 5 ff.); Sabine Kalff: Back to the cellar. Underground urban spaces of fear and air warfare in Berlin, 1940-1945 (S. 13 ff.); Aleksandra Łuczak: Fears and charms of mobility and transience. Warsaw's central railway station in the 20th century (S. 29 ff.); Clara Aßmann: „Die Straße war schuld!" Die Konstruktion eines Angstraums und der autogerechte Stadtumbau in der Bundesrepublik Deutschland (S. 51 ff.); Tim Verlaan: `The City is collapsing under our very own eyes'. Spaces and emotions of the Dutch urban crisis (S. 65 ff.); Monika Motylińska: Leitrezension (S. 82 ff.).

In this themed issue, we explore the dialectical relationship between the spatiality of 20th century European cities and a particular emotion - fear: from a physically palpable fear of bomb attacks, to the fear of traffic accidents instrumentalised in urban planning discussions, to more diffuse fears such as those associated with railway stations or post-war urban fear projections. By addressing different aspects, roots and shades of the tension between fear and urban space, we aim to offer new perspectives and insights into the emotional history of 20th century urban Europe.
Keywords: Angstraum; Niederlande; Polen; Warschau; Berlin; Berlin; Stadtraum; Angst; Unsicherheit; Kriminalität; Bedrohung; Bombardierung; Autoverkehr; Bahnhof; Zwanzigstes Jahrhundert; Stadtsoziologie; Stadtgeschichte